The intellectual structure of human resource management and digitalization research (2024)
An integrated analysis of the academic literature for comprehending and advancing in the human resource digital transformation is required. In this sense, this study aims to analyze the development, current status, and trends of the literature of human resource management research regarding its digital transformation. A total of 284 academic documents published between 2001 and 2022 in all fields of knowledge were retrieved from the Web of Science (WoS) database. Data was analyzed through VOSViewer software and bibliometrix R-package. According to the bibliometric analyses, from 2015 digital transformation of HRM had a sustained crescent interest being more remarkable since 2020. Foundational papers, the most influential documents, journals and authors were identified. Through a bibliographic coupling analysis, we identify five current mainstreams: 1) Impact, challenges and out-comes of e-HRM, 2) e-HRM and organizational strategy, 3) Conceptualization of strategic human resource management, 4) Effectiveness of e-HRM: productivity and performance, and 5) e-HRM and innovation. Co-word analysis shows clusters oriented to 1) digital platforms, 2) data analytics and 3) organizational strategy. All the conducted analyses show that human factors have received less attention, a finding confirmed by the thematic map. “Management, strategy, information” and “antecedents, quality and economic growth” are acquiring special relevance in structuring the research field of digital HRM according to the thematic map. These findings and their implications are discussed.